Quantum-Dot and Polychalcone Mixed Nanocomposites for Polymer Light-Emitting Diodes. (23rd October 2017) - Ramkumar, Vanaraj; Ju, Sanghyun
Abstract : The present work is aimed at improving the efficiency of light-emitting diodes (LEDs) through the amalgamation of polymeric materials and quantum dots (QDs) in nanocomposites. Herein, we report on the polytriphenylamine-based chalcone (PTpC) or polycarbazole-based chalcone- (PCzC-) QDs mixture nanocomposites as emissive layers for polymer LEDs (PLEDs). QDs were evenly dispersed in the polymer matrix and the synthesized PTpC-QDs and PCzC-QDs nanocomposites were able to form smooth thin films. The luminance characteristics of PTpC-QDs and PCzC-QDs nanocomposites were better than those of the pristine QD, PTpC, and PCzC materials, owing to the high charge-carrier transport ability of polymer-QDs nanocomposites. These results indicate that the proposed polymer-QDs nanocomposites could be potential candidates for application in PLEDs.